Vector‐Free Deep Tissue Targeting of DNA/RNA Therapeutics via Single Capacitive Discharge Conductivity‐Clamped Gene Electrotransfer - Jeremy L. Pinyon; Georg vonJonquieres; Stephen L. Mow; Amr Al Abed; Keng‐Yin Lai; Mathumathi Manoharan; Edward N. Crawford; Stanley H. Xue; Sarah Smith‐Moore; Lisa J. Caproni; Sarah Milsom; Matthias Klugmann; et al. (Advanced Science)
Abstract Viral vector and lipid nanoparticle based gene delivery have limitations around spatiotemporal control, transgene packaging size, and vector immune reactivity, compromising translation of nucleic acid (NA) therapeutics. In the emerging field of DNA and particularly RNA‐based gene therapies, vector‐free delivery platforms are identified as a key unmet need. Here, this work addresses these challenges through gene electrotransfer (GET) of “naked” polyanionic DNA/mRNA using a single needle form‐factor which supports “electro‐lens” based compression of the local electric field, and local control of tissue conductivity, enabling single capacitive discharge minimal charge gene delivery. Proof‐of‐concept studies for “single capacitive discharge conductivity‐clamped gene electrotransfer” (SCD‐CC‐GET) deep tissue delivery of naked DNA and mRNA in the mouse hindlimb skeletal muscle achieve stable (>18 month) expression of luciferase reporter synthetic DNA, and mRNA encoding the reporter yield rapid onset (<3 h) high transient expression for several weeks. Delivery of DNAs encoding secreted alkaline phosphatase and Cal/09 influenza virus hemagglutinin antigen generate high systemic circulating recombinant protein levels and antibody titres. The findings support adoption of SCD‐CC‐GET for vaccines and immunotherapies, and extend the utility of this technology to meet the demand for efficient vector‐free, precision, deep tissue delivery of NA therapeutics.